The use of tropical bromeliads (Tillandsia spp.) for monitoring - Brighigna, Luigi (2002)
The results of an experiment with two species of epiphytic angiosperms (Tillandsia caput-medusae and T. bulbosa) for monitoring polycyclic aromatic hydrocarbons (PAHs) in the air of Florence, Italy, are presented. PAHs are compounds known to be dangerous because of their carcinogenic potential, and among cormophytes, tillands (monocotyledons equipped with peculiar, specialised, epidermal trichomes) are considered promising for air pollution biomonitoring. PAHs data were obtained using GC/MS analysis of plant extracts. Analytical data indicated an increasing trend in time of PAHs bioaccumulation. This result was compared with instrumentally recorded parameters such as meteorological (rain) and environmental ones (PM10), indicating that trichome-operated physical capture of aerial particles was prominent in PAHs bioaccumulation on tillands. SEM (scanning electron microscope) observations confirmed the role of the trichomes. This work indicates that tillands are particularly useful, low-cost, biomonitoring organisms inside their area of distribution (all Latin American countries and southern USA) where these plants are easily available, but also wherever the climate allows them to survive.